Integration of renewable energy in markets: analysis of key European and American electricity markets - Algarvio, Hugo (2020)
ABSTRACT: Electricity markets are systems for affecting the purchase and sale of energy. Most existing markets are built on well-established principles of competition and transparency. However, their designs are based on centralized power plants with a small participation of end-use customers. During the past years, the share of electricity produced by renewable sources increased significantly. This paper analyses the structure and operation of two European markets and two American markets. The analysis highlights that the design, rules and characteristics of most markets are still not completely adapted to power systems with high levels of variable renewable energy. Accordingly, the paper proposes some recommendations to foster the integration of renewable generation.